Corrections of the methods for manganese determination in waste waters by UV-VIS spectrophotometry and atomic absorption spectrometry and investigation of the possibility for its precipitation - Stafilov, Trajče (Macedonian Journal of Ecology and Environment, 1994)
Corrections of the methods for determination of manganese in waste waters by ultraviolet-visible and atomic absorption spectrometry were proposed^ A method for spectrophotometric determination of manganese by previous oxidation in permanganate ion, has to be corrected whenever iron is present in the water samples with concentrations higher than 2000 mg • dm"3. The influence of iron was also found in the manganese determination by atomic absorption spectrometry. The iron present (in the concentration higher that 500 mg-dm"3), decreases the absorbance of manganeseaccording to the (empirically) found relation : γMn = 3,605 * γFe * γMn(found) + 0.996 * γFe(found) The investigations show that chloride ions do not influence on the manganese determination by AAS even they are present in concentration up to 5000 mg • dm"3. The investigation of the possibility of elimination of manganese from waste water shows, that, by adding of saturated solution of Са(ОН)г , in the presence of iron(III) ions, it is possible to precipitate most of the manganese (the iron also precipitates). The optimum value of pH is about 7.